Comparison of Low Dose Ketamine Versus Normal Saline in Prevention of Postoperative Shivering - Roheena Wadud, Beena Khan, Imran Ul Haq, Abdullah Babar, Khayyam Farid, Tanzeela Firdous (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Shaking is a frequent adverse effect of anesthesia, which may potentially exacerbate the discomfort. It is characterized by involuntary muscular contractions that can affect many muscle groups. It is extremely unpleasant and physically demanding. Objective: The purpose of this study is to examine the efficacy of Low Dose Ketamine against normal saline in preventing postoperative trembling. Study Design: Randomized Controlled Trial. Setting: Department of Anesthesiology, Khyber Teaching Hospital, Peshawar. Duration of Study: This study was conducted from 1st July 2020 to 31st December 2020. Subjects and Methods: Sixty male and female patients who volunteered for lower abdominal surgery were studied. Each block of six was shuffled before the randomization procedure began. Thirty people made up the Low Dose Ketamine group (A), and the Normal Saline group (B) (B). After 30 minutes, the Crossley and Mahajan scale was used to measure the degree to which both groups were shivering after the surgical incisions had healed. This was done so that we could gauge the accuracy of the measuring device. Results: Age range in this study was from 20 to 60 years. Efficacy was observed in 28 (93.3%) patients in group A as compare to 16 (53.3%) patients in group B (P= 0.000). Conclusion: As a consequence of this research, it appears that 0.25 mg/kg of ketamine is an effective dose for minimizing postoperative shivering after elective surgery. Keywords: Postoperative shivering, Low dose ketamine, Efficacy